Adiponectin gene polymorphisms and susceptibility to diabetic nephropathy: a meta-analysis. (April 2014) - Lin, Zi; Huang, Guoliang; Zhang, Jingwen; Lin, Xiaoyu
Abstract Adiponectin (ADIPOQ) plays an important role in the pathogenesis of diabetic nephropathy (DN) and previous studies regarding the association between ADIPOQ polymorphisms and DN risk reported conflicting results. To derive a more precise estimation of this association, we performed a meta-analysis to assess the association between four ADIPOQ polymorphisms [−11391G > A (rs17300539), −11377C > G (rs266729), +45T > G (rs2241766), and +276G > T (rs1501299)] and risk for DN. Odds ratios (ORs) with corresponding 95% confidence intervals (95% CIs) were pooled to assess the association between four aforementioned polymorphisms and susceptibility to DN. Based on the included criteria, we selected 13 articles, among which 7 studies (cases/controls: 2749/7585) for −11391G > A, 8 studies for −11377C > G (3074/3842), 9 studies for +45T > G (2654/7710), and 10 studies for +276G > T (2812/7821), respectively. Our meta-analysis indicated no evidence heterogeneity among the included studies; thus, the fixed-effects model was used. Overall, there was an association between ADIPOQ −11391A allele with increased DN risk (OR = 1.186, 95% CI: 1.051–1.338, p = 0.006). Subgroup by ethnicity suggested significant association between +45T > G polymorphism and DN risk among Caucasians (OR = 1.122, 95% CI: 1.007–1.250, p = 0.038). Sensitivity analysis suggested exclusion of any single study did not materially alter the overall pooled ORs above. Future studies are needed to validate these findings.